2008
DOI: 10.1093/ajcn/87.3.704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal food and micronutrient supplementation on infant development: a randomized trial from the Maternal and Infant Nutrition Interventions, Matlab (MINIMat) study

Abstract: Small benefits from early food and MM supplementation were found in infants of low-BMI but not of high-BMI mothers. However, the benefits were of doubtful functional importance, and longer follow-up is required to determine programmatic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 149 publications
(167 citation statements)
references
References 28 publications
6
160
1
Order By: Relevance
“…This review found some evidence that multivitamin and mineral supplementation might positively influence certain aspects of brain development in children (Leung et al, 2011). The review included six trials on multiple-micronutrient supplementations conducted in Peru, rural Taiwan, Tanzania (on HIV infected mothers), and in rural China, Indonesia and Bangladesh, where mothers were poorly nourished (Joos et al, 1983;Schmidt et al, 2004;McGrath et al, 2006;Tofail et al, 2008;Li et al, 2009;Caulfield et al, 2010). A very recent randomized controlled trial in Indonesia found that multiple micronutrient supplementation in undernourished pregnant mothers resulted in improved motor development, visual attention and spatial ability in pre-schoolers (Prado et al, 2012).…”
Section: Multivitamin and Mineral Supplementationmentioning
confidence: 99%
“…This review found some evidence that multivitamin and mineral supplementation might positively influence certain aspects of brain development in children (Leung et al, 2011). The review included six trials on multiple-micronutrient supplementations conducted in Peru, rural Taiwan, Tanzania (on HIV infected mothers), and in rural China, Indonesia and Bangladesh, where mothers were poorly nourished (Joos et al, 1983;Schmidt et al, 2004;McGrath et al, 2006;Tofail et al, 2008;Li et al, 2009;Caulfield et al, 2010). A very recent randomized controlled trial in Indonesia found that multiple micronutrient supplementation in undernourished pregnant mothers resulted in improved motor development, visual attention and spatial ability in pre-schoolers (Prado et al, 2012).…”
Section: Multivitamin and Mineral Supplementationmentioning
confidence: 99%
“…Nine of these (conducted in Bangladesh; Burkina Faso; China; Guinea-Bissau; Lombok, Indonesia; Indramayu, Indonesia; Janakpur, Nepal; Niger; and Pakistan) [5][6][7][8][9][10][11][12][13] used UNIM-MAP (see table 1), and the other three (conducted in Mexico [14]; Sarlahi, Nepal [15]; and Zimbabwe [16]) used other multiple micronutrient supplements. The composition of the supplements used in these trials is summarized in table 1.…”
Section: Studies Includedmentioning
confidence: 99%
“…Supplementation benefits on children' s cognition were apparent at 7 months of age but not at 18 or 64 months. 12,13 We therefore combine the groups and treat them as a cohort study for this article. We hypothesized that poverty is associated with cognitive deficits, and parental education, pre-and postnatal growth, and home stimulation would mediate the effects of poverty on cognition.…”
mentioning
confidence: 99%